PENINGKATAN HASIL BELAJAR PJOK MELALUI METODE DEMONSTRASI DAN LATIHAN PADA SISWA SEKOLAH MENENGAH - Rafikaardila; Mutia, Rahel; Mufidah; Joel; Wanri; Tommy; Ibrena (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Physical Education, Sports, and Health (PJOK) learning plays an important role in improving students' physical abilities, motor skills, and sportsmanship. However, in practice, the learning process is often teacher-centered, resulting in students being less active in participating in learning activities. This study aims to improve student learning outcomes through the application of demonstration and practice methods in PJOK learning. This study uses a Classroom Action Research (CAR) approach implemented in two cycles consisting of planning, action implementation, observation, and reflection. The research subjects were high school students. Data collection techniques were carried out through observation, learning outcome tests, and documentation. The results of the study indicate that the application of demonstration methods accompanied by repeated practice can improve students' understanding and skills in participating in PJOK learning. Thus, the demonstration and practice method can be an effective alternative learning strategy to improve student learning outcomes.